SIKLUS MEGA-TSUNAMI DI WILAYAH ACEH-ANDAMAN DALAM KONTEKS SEJARAH - Danny Hilman Natawidjaja (Indonesian Institute of Sciences, 2015)
Abstract Mega‐tsunami Aceh‐Andaman 2004 revolutionary changed people awareness of earthquakes and tsunami threats. The event also caused major changes in politics and social infrastructures, from a period of terror to a new government of NAD. Paleoseismological studies indicate two penultimate tsunami events prior to 2004 around 1390 AD and 1440 AD. These are confirmed by the GPS study suggesting the 2004-like event (Mw9.15) can be repeated every six hundred years. In 1236 AD, the well known Islamic state, Samudra Pasai, was arise, marking a new era in Aceh. After 1450 AD, Samudra Pasai seems to be slowly dissapeared. Later in 1496 AD, a new Islamic Kingdom, Aceh Darussalam, appeared and dominated the Aceh region. It is strongly suspected that the changes of power from Samudra Pasai to Aceh Darussalam was linked to the mega‐tsunami events in 1390 and 1440 AD. Understanding ancient natural catastrophic and the affected society is crucial in developing awareness and in natural‐dissaster mitigations, including to rejuvinate a true local wisdomAbstrak Mega tsunami di wilayah Aceh-Andaman pada tahun 2004 merubah masyarakat menjadi melek terhadap ancaman bencana gempa dan tsunami . Bencana 2004 merubah pemerintahan dan tatanan masyarakat di Aceh, dari masa teror ke pemerintahan NAD yang baru. Penelitian paleoseismologi menguak peristiwa bencana gempa-tsunami tahun sebelumnya, sekitar tahun 1390 M dan 1450 Masehi. Fakta ini ditunjang oleh data tektonik geodesi (GPS) bahwa siklus perulangan gempa 2004 (Mw9.15) dapat terjadi sekitar 600 tahunan sekali. Pada tahun 1236, berdirinya Kerajaan islam Samudra Pasai yang cukup dikenal menandai era baru di Aceh. Setelah tahun 1450 Masehi, Kerajaan Samudra Pasai ini seperti meredup dan menghilang. Kemudian pada tahun 1496 Masehi berdiri Kerajaan Baru Islam, Aceh Darussalam yang tidak ada hubungannya dengan Samudra Pasai. Diduga peralihan masa Samudra Pasai ke masa Aceh Darussalam berkaitan erat dengan kejadian tsunami tahun 1390 dan 1440 Masehi tersebut. Memahami kejadian bencana katastropik purba dan masyarakat yang terkena dampaknya adalah aspek yang sangat penting dalam pendidikan kebencanaan, khususnya dalam mengembangkan kesiapsiagaan dan kearifan lokal.